Multicore Systems ready or not, here they come. - Pasker, Bob
Every major chip manufacturer has delivered or announced a roadmap for multicore chips that have multiple CPUs on the same piece of silicon. Systems developers are now designing these chips into their entire product line. For Java platform developers, Symmetric Multiprocessing Systems (SMP) should be hidden well below the hardware abstraction layer, but not all applications will get equal benefits from SMP without understanding what's going on under the hood.